Feline Coronavirus infections and feline infectious peritonitis - TZIVARA (Α. ΤΖΙΒΑΡΑ) A.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Cats are susceptible to infection with several different strains of feline Coronavirus. Depending on the involved strain, clinical signs may range from asymptomatic infection to gastrointestinal disease or fibrinous serositis and disseminated vasculitis, commonly known as feline infectious peritonitis (FIP). Excretion of virus by infected cats into the environment occurs by faeces, oronasal secretions and urine. The feline coronaviruses are rapidly inactivated by most disinfectants. Clinical diagnosis of Coronavirus infection is made by evaluating the case history, physical findings, laboratory results, Coronavirus antibody titers and tissue biopsy. A temperature-sensitive feline infectious peritonitis virus vaccine has become available for healthy 16 week of age or older cats.